Duindam, Dynasties: A Global History of Power, 1300-1800 (Cambridge University Press, 2015) - Derek R Whaley (Royal Studies Journal, 2017)
Review of Jeroen Duindam, Dynasties: A Global History of Power, 1300-1800 (Cambridge: Cambridge University Press, 2016).